The Impact of Exports and Imports of Services on Gross Domestic Product (GDP) in Syria (1980-2017) - شريقي, طرفة; حسيكة, خليل (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Trade in services today plays a prominent role in the midst of international trade along with merchandise trade and thus contributes to the rotation of the wheel of the global economy. Accordingly, this research came to light on the international services trade and standing on it in two levels: 1(globally), Knowing its size and percentage of GDP, 2(Syria) Knowing its size and studying the existence of a significant effect of services exports and imports on the GDP (1980-2010). The research concluded that the Syrian services trade has developed at a better and better than the Syrian goods trade during the study period. Since 2004, the Syrian services balance has managed to achieve a surplus that enabled it to reduce the current account deficit resulting from the deficit of the trade balance (commodity). The research showed a direct correlation between Syrian services exports and imports and the Syrian GDP.